PREVALENCE OF BOVINE ENZOOTIC HEMATURIA DETECTED BY URINALYSIS IN OXAPAMPA, PERU - Herencia B., Karina (2013)
Bovine Enzootic Vesical Hematuria (BEVH) is a disease caused by continuous consumption of the common fern (Pteridium aquilinum). This plant has a set of carcinogenic and mutagenic substances, including the ptaquiloside (pq) which is responsible for neoplastic and hemorrhagic lesions in the bladder mucosa of cattle, eventually leading to hematuria. This study determined the prevalence of BEVH in cattle at Chontabamba, province of Oxapampa, Peru. Urine samples were collected by perianal massage from 210 females older than 2 years old of various genotypes and productive purpose (milk and beef). The animals were naturally exposed to consumption of the common fern. Urine samples were subject to urianalysis test involving the application of urine test strips (UTS) and microscopic examination of urinary sediment (MEUS). The prevalence of BEVH was 7.6 ± 3.6% by UTS and 15.2 ± 4.9% by MEUS. The prevalence was higher in 1.5 to 4 year old animals. There was no statistical association between presence of BEVH with breed or productive purpose. It is concluded that this geographic area is endemic to BEVH.